Reseña bibliográfica de : La enseñanza del Derecho como forma de acción política, de Duncan Kennedy - Varela, Agustín (2013)
This work is a review of the papers written by Duncan Kennedy, which were translated and compiled on the book Law teaching as political action. Kennedy, Professor at Harvard University and one of the most renowned members of the Critical Legal Studies, invites us to think about the function of Law and the traditional way of conceiving it that is reproduced in Law Schools. He explains in a clear and simple way his conception of Law and also outlines ways to teach it. In this article we make a brief review of each of the papers that are included in the book.